Computerized Accounting Systems and Financial Performance of General Merchandise Businesses in Uganda (Case Study of Novo Enterprises Limited, Tororo) - Sharon Agnes Nyamwenge (Uganda Christian University, 2025)
The study examined the relationship between Computerized Accounting Systems and financial performance of General Merchandise businesses in Uganda, A case of Novo Enterprises Limited, Tororo Branch. The study was based on three specific objectives including examining the relationship between computerized data filing and financial performance of NEL, determining the relationship between computerized data storage and financial performance of NEL and assessing the relationship between computerized data retrieval and financial performance of Novo Enterprises Limited. Theoretically, this study was underpinned by the Technology Acceptance Model theory. This study used across-sectional survey design with both qualitative and quantitative approaches. The population of the study was 150 employees with a sample size of 100 employees. The study employed both purposive and simple random sampling. Findings from the study show that Computerized Record Storage is the greatest contributor to financial performance with beta value = 0.551 at 0.001 level of significance. This means that Computerized Record storage has a positive and significant effect on financial performance. Findings from the study reveal that Computerized Record Filling is the second contributor to financial performance with beta value = 0.439 at .003 level of significance. This means that Computerized Record filling has a positive and significant effect on financial performance. Findings from the study show that Computerized Record Retrieval is the third contributor to financial performance with beta value = 0. 342 at .931 level of significance. This signifies that Computerized Record Retrieval has a positive and significant effect on financial performance. Findings from the model summary using predictors including Computerized Record Filling, Computerized Record Storage, and Computerized Record Retrieval produced Adjusted R Square value of 0.971. This shows that 97.1% variations in financial performance are caused by Computerized Record Filling, Computerized Record Storage, Computerized Record Retrieval while the remaining 2.9% variations in financial performance are as a result of other factors. According to the study, Novo Enterprises Limited's management should make sure that financial records are kept up to date and reported objectively at all times. This could enhance the standards of financial data handed in, which could assist in decision-making and enhance Novo Enterprises Limited’s financial performance. The results of the study showed that computerized record retrieval significantly improves financial performance. The study suggests Novo Enterprises Limited’s management undertake an investment in database development to provide simple data backup, archiving, and retrieval as needed. The management of NEL should make sure that records are properly preserved in safe locations for a suitable amount of time in order to improve financial performance, based on the fact that records storage has a positive and significant effect on the financial performance